2021
DOI: 10.3389/fonc.2021.568568
|View full text |Cite
|
Sign up to set email alerts
|

Best Supportive Care Versus Whole-Brain Irradiation, Chemotherapy Alone, or WBRT Plus Chemotherapy in Patients With Brain Metastases From Small-Cell Lung Cancer: A Case-Controlled Analysis

Abstract: BackgroundWBRT and systemic chemotherapy are the mainstay treatments for small-cell lung cancer (SCLC) brain metastases (BM). However, current recommendations are mainly based on evidence from retrospective analyses. A recent randomized trial found no benefits from WBRT compared with best supportive care (BSC) in patients with more than three BM from non-small-cell lung cancer (NSCLC). Herein, we aimed to evaluate the roles of WBRT and chemotherapy further in the management of BM from SCLC.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…[ 24 ]. After WBRT, local radiotherapy for NSCLC patients with brain metastasis can reduce the treatment target volume, improve the tumor control rate, reduce local recurrence and the occurrence of intracranial new tumors, and relieve the clinical symptoms of patients to some extent [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ]. After WBRT, local radiotherapy for NSCLC patients with brain metastasis can reduce the treatment target volume, improve the tumor control rate, reduce local recurrence and the occurrence of intracranial new tumors, and relieve the clinical symptoms of patients to some extent [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with a limited number of BMs, an additional radiation boost to WBRT or SRT can be recommended [ 16 , 17 ]. Several studies have suggested that the occurrence of BMs is a sign of systemic failure of tumor control; therefore, the treatment of BMs should focus on chemoradiotherapy [ 20 , 21 , 22 ]. A respective study in 2021 observed that the combination of WBRT and etoposide-platinum agents could prolong OS in SCLC patients with BMs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the occurrence of BMs is a sign of systemic failure of tumor control; therefore, the treatment of BMs should focus on chemoradiotherapy [ 20 , 21 , 22 ]. A respective study in 2021 observed that the combination of WBRT and etoposide-platinum agents could prolong OS in SCLC patients with BMs [ 21 ]. However, another prospective trial did not obtain similar results [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, patients with lung cancer parotid metastasis seem to show a greater tendency of brain metastasis. Previous studies concluded that WBRT ( 60 , 61 ), stereotactic radiosurgery (SRS) ( 62 , 63 ), and prophylactic cranial irradiation (PCI) ( 62 , 64 , 65 ) can improve the prognosis of these patients and bring survival benefits. Therefore, for patients for whom brain metastasis already appears, WBRT or SRS should be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%